2016
DOI: 10.1590/0004-282x20160050
|View full text |Cite
|
Sign up to set email alerts
|

Collateral blood vessels in acute ischemic stroke: a physiological window to predict future outcomes

Abstract: Collateral circulation is a physiologic pathway that protects the brain against ischemic injury and can potentially bypass the effect of a blocked artery, thereby influencing ischemic lesion size and growth. Several recent stroke trials have provided information about the role of collaterals in stroke pathophysiology, and collateral perfusion has been recognized to influence arterial recanalization, reperfusion, hemorrhagic transformation, and neurological outcomes after stroke. Our current aim is to summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 68 publications
0
21
0
1
Order By: Relevance
“…Všech pět pacientů (4,5 %) se symptomatickým intrakraniálním krvácením zemřelo. Detailní charakteristika pacientů obou skupin je uvedena v tabulce 2. fi citem a menším objemem infarzované mozkové tkáně [25,26]. Naše výsledky mohou být ovlivněny skutečností, že v naší studijní skupině byli kuřáci mladší než nekuřáci (68,1 vs. 62,4, p = 0,01).…”
Section: Výsledkyunclassified
“…Všech pět pacientů (4,5 %) se symptomatickým intrakraniálním krvácením zemřelo. Detailní charakteristika pacientů obou skupin je uvedena v tabulce 2. fi citem a menším objemem infarzované mozkové tkáně [25,26]. Naše výsledky mohou být ovlivněny skutečností, že v naší studijní skupině byli kuřáci mladší než nekuřáci (68,1 vs. 62,4, p = 0,01).…”
Section: Výsledkyunclassified
“…The last decade was marked by studies employing the endovascular treatment of intrac-ranial and extracranial occlusions, and it was only recently that several studies confirmed that mechanical thrombectomy following the endovascular approach is superior to standard treatment with or without intravenous thrombolysis [7]. However, the outcomes after these treatments are still variable and do not depend only on the method, but also on specific biological characteristics of the patient [8].…”
Section: Acute Ischemic Strokementioning
confidence: 99%
“…The degree of development of collateral circulation also affects the size of the infarct lesion. All these findings have put the relationship between collaterals and the possibility of predicting the evolution of infarction and clinical outcome after AIS in the focus of scientific interest in recent years [8,13].…”
Section: Acute Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Anastomotic connections of the cortical surface and interconnections of subsurface microvasculature are the two principal connections underlying the collateral vasculature . Previous studies have found that extensive anastomotic connections facilitate partial reperfusion of ischemic territories after focal stroke . However, the potential recruitment of subsurface microvessels and their contribution to focal ischemia are yet to be studied because of the limitation of imaging technique and animal models.…”
Section: Introductionmentioning
confidence: 99%